2017
DOI: 10.3892/ol.2017.6739
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin inhibits cell proliferation and promotes apoptosis of laryngeal cancer cells through Bcl-2 and PI3K/Akt, and by upregulating miR-15a

Abstract: Abstract. Curcumin is a natural compound extracted from the dried rhizomes of Curcuma (curcuma root or zedoary) that exhibits extensive pharmacological effects and low toxicity. The aim of the present study was to investigate whether curcumin inhibits cell proliferation and promotes apoptosis of laryngeal cancer through Bcl-2 and phosphoinositide 3-kinase (PI3K)/protein kinase B (Akt), and by upregulating microRNA-15a (miR-15a). It was demonstrated that curcumin inhibits cell proliferation, and promotes apopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 26 publications
2
32
0
Order By: Relevance
“…In agreement with our results, a recent study has reported similar behavior of curcumin, in that high doses of curcumin (10 µM) resulted in the apoptosis of malignant cells and a low dose of curcumin (0.5 µM) elevated the proliferation rate, migration and phagocytosis of olfactory ensheathing cells (OECs) favorable for neural regeneration (Tello Velasquez et al, 2014[ 45 ]). Earlier studies have established that reduced cell viability in curcumin-treated tumor cells was accompanied by the repression of signaling proteins such as NF-ƙB and Notch-1, blocking downstream genes like vascular endothelial growth factor (VEGF), Bcl2 and matrix metalloproteinase (Marquardt et al, 2015[ 25 ]; Mou et al, 2017[ 30 ]; Pavan et al, 2016[ 34 ]). The same mechanisms may be involved in the apoptosis and proliferation of AT-MSCs after exposure to high concentrations of micelle-encapsulated curcumin.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with our results, a recent study has reported similar behavior of curcumin, in that high doses of curcumin (10 µM) resulted in the apoptosis of malignant cells and a low dose of curcumin (0.5 µM) elevated the proliferation rate, migration and phagocytosis of olfactory ensheathing cells (OECs) favorable for neural regeneration (Tello Velasquez et al, 2014[ 45 ]). Earlier studies have established that reduced cell viability in curcumin-treated tumor cells was accompanied by the repression of signaling proteins such as NF-ƙB and Notch-1, blocking downstream genes like vascular endothelial growth factor (VEGF), Bcl2 and matrix metalloproteinase (Marquardt et al, 2015[ 25 ]; Mou et al, 2017[ 30 ]; Pavan et al, 2016[ 34 ]). The same mechanisms may be involved in the apoptosis and proliferation of AT-MSCs after exposure to high concentrations of micelle-encapsulated curcumin.…”
Section: Discussionmentioning
confidence: 99%
“…PI3K/Akt signaling is regarded as a classic anti-apoptotic pathway [38] [39]. PI3K has three classes; I, II, and III.…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin could increase ROS production and apoptosis in C. albicans cells, either alone or in synergy with antifungal drugs such as azoles and polyenes [ 78 , 79 ]. In mammalian cells, curcumin could protect mitochondria from damage and increase the biogenesis of mitochondria, although apoptosis-inducing effects of curcumin have also been reported in cancer cells [ 80 , 81 ]. Most importantly, this compound could be safe with a maximum tolerance dose of 12,000 mg/day in Phase I clinical trials [ 82 ], which present an advantage over other antifungal compounds.…”
Section: Compounds Targeting Mitochondriamentioning
confidence: 99%